2023
DOI: 10.1002/vms3.1190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strontium ranelate and cerium oxide addition in the diet on bone quality and expression level of osteocalcin and alkaline phosphatase genes in broiler chicken

Abstract: Background: In the modern broiler industry, leg and gait disorders are considerable problems. Fast-growing broilers are especially susceptible to bone abnormalities, causing major problems for broiler producers. Strontium ranelate (SrR) has been used successfully for the treatment of osteoporosis in humans. In addition, cerium oxide (CeO) is an anti-stress agent applied in the biological system.Methods: This study was conducted to investigate the effect of SrR, CeO, and their combinations on tibia quality in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…The results of serum biochemistry showed that the ALP content of High group was significantly increased (P<0.05). During bone growth and development, bone cells became active and produced a large number of ALP into the blood, promoting bone growth and development ( 57 , 58 ). At this dose, TMAE also reduced CRE in broiler serum (P<0.05) and increased BUN at Medium dose, but the study showed that except UA, other biochemical indicators reflecting renal function lacked specificity in the assessment of renal health in birds, which was closely related to the special physiological system of birds ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of serum biochemistry showed that the ALP content of High group was significantly increased (P<0.05). During bone growth and development, bone cells became active and produced a large number of ALP into the blood, promoting bone growth and development ( 57 , 58 ). At this dose, TMAE also reduced CRE in broiler serum (P<0.05) and increased BUN at Medium dose, but the study showed that except UA, other biochemical indicators reflecting renal function lacked specificity in the assessment of renal health in birds, which was closely related to the special physiological system of birds ( 59 ).…”
Section: Discussionmentioning
confidence: 99%